Are Endothelial Progenitor Cells the Real Solution for Cardiovascular Diseases? Focus on Controversies and Perspectives. (5th October 2015) - Balistreri, Carmela R.; Buffa, Silvio; Pisano, Calogera; Lio, Domenico; Ruvolo, Giovanni; Mazzesi, Giuseppe
Abstract : Advanced knowledge in the field of stem cell biology and their ability to provide a cue for counteracting several diseases are leading numerous researchers to focus their attention on "regenerative medicine" as possible solutions for cardiovascular diseases (CVDs). However, the lack of consistent evidence in this arena has hampered the clinical application. The same condition affects the research on endothelial progenitor cells (EPCs), creating more confusion than comprehension. In this review, this aspect is discussed with particular emphasis. In particular, we describe biology and physiology of EPCs, outline their clinical relevance as both new predictive, diagnostic, and prognostic CVD biomarkers and therapeutic agents, discuss advantages, disadvantages, and conflicting data about their use as possible solutions for vascular impairment and clinical applications, and finally underline a very crucial aspect of EPCs "characterization and definition, " which seems to be the real cause of large heterogeneity existing in literature data on this topic.